RISK ASSESSMENT PENYAKIT AKIBAT PAPARAN BAHAN KIMIA PADA UNIT PREMIX - Rieneke Puspita Eka Suci (Universitas Airlangga, 2018)
PT. Japfa Comfeed is one of poultry companies, in production of poultry needed feed additive to improve quality of poultry. Premix unit is unit that production feed additive for poultry. There are some hazards in process of premix production. Therefore, to prevent health problems, risk assessment is needed. The objective of this study is risk assessing at premix production PT. Japfa Comfeed Indonesia Tbk. Unit Gedangan. This research is a descriptive study. The population of this research were 15 person premix unit worker and 1 (one) safety officer at PT. Japfa Comfeed Indonesia Tbk. Unit Gedangan. The result of the research showed that there were chemical hazard, such as feed additives and meat and bone meal (MBM). Based on hazard identification obtained 34 risk with 76.5%medium risks and 23.5% low risks. Risk control on feed additive unit at PT. Japfa Comfeed Indonesia Tbk. Unit Gedangan was categorizes as good enough. This is due to risk control effort, such as engineering control, administrative control, and Personal Protective Equipment, such respiratory and glove. However, those efforts had not been fully applied by feed additive worker. Residual risk assessment showed that risk control needs to be reset to reduce the risk. Conclusion that can be drawn is process in premix unit categorized as medium risk.Keywords: poultry, premix, risk assessment